PERAN INTERAKSI VIRTUAL DALAM SOCIAL COMMERCE TERHADAP KEPERCAYAAN DAN LOYALITAS KONSUMEN DI INDONESIA - Ina Yulianadewi; Yuyu Ruhayu; Fera Firyal Thahir (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to analyze the role of virtual interaction in social commerce on consumer trust and loyalty in Indonesia. The rapid growth of social media–based commerce has made virtual interaction a crucial factor in shaping relationships between sellers and buyers in the digital space. A quantitative approach was employed through a survey of 250 active users of social commerce platforms such as TikTok Shop, Shopee Live, and Instagram Shop. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method to examine the relationships among variables. The findings reveal that virtual interaction has a positive and significant effect on both consumer trust and loyalty. Consumer trust also positively affects loyalty and mediates the relationship between virtual interaction and consumer loyalty. These results indicate that trust serves as a key element linking digital interaction activities to customer loyalty formation. Theoretically, this study enriches the literature on social commerce and relationship marketing by confirming the relevance of the Social Exchange Theory and Online Trust Theory in Indonesia’s digital context. Practically, the results suggest that business practitioners should strengthen virtual communication with consumers through responsive, empathetic, and transparent interactions while utilizing features such as live streaming, interactive chat, and user reviews to foster trust and loyalty. The study also provides insights for platform managers and regulators to enhance transaction security, transparency, and consumer digital literacy.